Peripheral impairments of oxidative metabolism after a 10‐day bed rest are upstream of mitochondrial respiration. (28th September 2021) - Zuccarelli, Lucrezia; Baldassarre, Giovanni; Magnesa, Benedetta; Degano, Cristina; Comelli, Marina; Gasparini, Mladen; Manferdelli, Giorgio; Marzorati, Mauro; Mavelli, Irene; Pilotto, Andrea; Porcelli, Simone; Rasica, Letizia; et al.
Abstract : Abstract: In order to identify peripheral biomarkers of impaired oxidative metabolism during exercise following a 10‐day bed rest, 10 males performed an incremental exercise (to determine peak pulmonary V̇O2 (V̇O2 p )) and moderate‐intensity exercises, before (PRE) and after (POST) bed rest. Blood flow response was evaluated in the common femoral artery by Eco‐Doppler during 1 min of passive leg movements (PLM). The intramuscular matching between O2 delivery and O2 utilization was evaluated by near‐infrared spectroscopy (NIRS). Mitochondrial respiration was evaluated ex vivo by high‐resolution respirometry in isolated muscle fibres, and in vivo by NIRS by the evaluation of skeletal muscle V̇O2 (V̇O2 m ) recovery kinetics. Resting V̇O2 m was estimated by NIRS. Peak V̇O2 p was lower in POST vs . PRE. The area under the blood flow vs . time curve during PLM was smaller ( P = 0.03) in POST (274 ± 233 mL) vs . PRE (427 ± 291). An increased ( P = 0.03) overshoot of muscle deoxygenation during a metabolic transition was identified in POST. Skeletal muscle citrate synthase activity was not different ( P = 0.11) in POST (131 ± 16 nmol min –1  mg –1 ) vs . PRE (138 ± 19). Maximal ADP‐stimulated mitochondrial respiration (66 ± 18 pmol s –1  mg –1 (POST) vs . 72 ± 14 (PRE), P = 0.41) was not affected by bed rest. Apparent K m for ADP sensitivity of mitochondrial respiration was reduced in POST vs . PRE ( P = 0.04). The V̇O2 m recovery time constant was not different ( P = 0.79) in POST (22 ± 6 s) vs . PRE (22 ± 6). Resting V̇O2 m was reduced by 25% in POST vs . PRE ( P = 0.006). Microvascular‐endothelial function was impaired following a 10‐day bed rest, whereas mitochondrial mass and function (both in vivo and ex vivo ) were unaffected or slightly enhanced. Key points: Ten days of horizontal bed rest impaired in vivo oxidative function during exercise. Microvascular impairments were identified by different methods. Mitochondrial mass and mitochondrial function (evaluated both in vivo and ex vivo ) were unchanged or even improved (i.e. enhanced mitochondrial sensitivity to submaximal [ADP]). Resting muscle oxygen uptake was significantly lower following bed rest, suggesting that muscle catabolic processes induced by bed rest/inactivity are less energy‐consuming than anabolic ones. Abstract : Abstract figure legend Potential sites of impairment of oxidative metabolism during exercise following microgravity‐inactivity.